Comparison on Clinicopathological Features and Prognosis Between Esophagogastric Junctional Adenocarcinoma (Siewert II/III Types) and Distal Gastric Adenocarcinoma. Issue 34 (August 2015) - Liu, Kai; Zhang, Weihan; Chen, Xiaolong; Chen, Xinzu; Yang, Kun; Zhang, Bo; Chen, Zhixin; Zhou, Zongguang; Hu, Jiankun; Maria, Kapritsou.
<x xml:space="preserve">Abstract</x> Abstract The incidence of the EGJA is rapidly increasing. The clinicopathological features have not yet been elucidated. The aim of this study was to analyze the differences in clinicopathological features and prognosis between patients with esophagogastric junctional adenocarcinoma (EGJA) and distal gastric adenocarcinoma (DGA). In this retrospective study, 1230 patients who underwent gastrectomy between January 2006 and December 2010 in West China Hospital were enrolled. Patients were divided into 2 groups based on tumor location. Clinicopathological characteristics, postoperative complications, and survival outcomes were compared. Univariate and multivariate analysis were also used to evaluate the prognostic factors of DGA and EGJA. Patients with gastric adenocarcinoma were divided into 2 study groups according to tumor location: 321 EGJA (26.1%) and 909 DGA (73.9%). Tumors with larger diameter, more advanced pT and pN stage were more common in EGJA. Significant differences were revealed in 3-year overall survival rate (3-YS) between 2 groups: EGJA (57.5%) and DGA (65.5%) (P = 0.001), and further analysis indicate that there was also significant difference on 3-YS between EGJA (76.9%) and DGA (84.2%) (P = 0.012) in stage II. From our multivariate analysis, we found that there were different independent prognostic indicators for DGA and EGJA. The clinicopathological features of EGJA were strikingly different from DGA and patients with EGJA showed a worse prognosis when compared with DGA. The pT stage, pN stage, pM stage, tumor size, age, and radical degree were determined to be independent factors of prognosis for DGA, while only combined organ resection, pN stage, and pM stage were independent prognostic factors for EGJA.